The Impact of Local Dialect on Speaking Skill of Students in Technical Department at Politeknik Pelayaran Barombong - Subhan Rahmat (Journal of English Language Teaching, Literature and Culture, 2024)
This study investigates the influence of the local dialect on students speaking abilities focusing specifically on the Makassar Gowa dialect It examines how the accent and features of the students first language can affect their proficiency in speaking English particularly in multicultural contexts The research explores challenges arising from dialectal interference and factors related to the mother tongue that impact oral performance Using a quantitative descriptive method data were collected through closed ended questionnaires The findings reveal that the local dialect plays a multifaceted role in shaping students speaking skills While dialectal influence poses certain challenges it also has positive implications Students who embrace their local dialect tend to exhibit greater confidence and motivation in learning English Moreover leveraging the local dialect in teaching strategies encourages active learning and enhances oral communication Teachers can utilize these insights to create a supportive learning environment incorporating various media and facilities to improve students speaking proficiency This study highlights the importance of understanding linguistic diversity in educational settings and underscores the potential of dialect sensitive approaches to foster better engagement and learning outcomes for English language learners< em>< p>